Body awareness in healthy subjects - a qualitative study - Kjölstad, Gunhild; Gyllensten, Amanda Lundvik; Gard, Gunvor (European journal of physiotherapy, 2022)
Qualitative research concerning body awareness has focused on how patients with different diagnosis experience body awareness. No earlier study has focused on healthy adults' experiences of body awareness. The aim of this study was to explore and describe healthy adults' experiences of body awareness. Fifteen healthy informants were interviewed individually, and the transcripts were analysed according to qualitative content analysis. Three themes describing experiences of body awareness among healthy adults: A bodily grounding and identity forming process throughout life, Interpersonal relationships through the body, and To be visible and exposed in society. Body awareness among healthy adults was experienced as a bodily and identity forming process throughout life. In this process interpersonal relationships were developed through the awareness of the body. Body awareness was also experienced as being visible and exposed in society. Body awareness was not only related to individuals experiences and affects our relations and behaviours from inside and out but was also related to group norms and societal norms. This is important for health promotion in different contexts in society.